Pengaruh Gaya Kepemimpinan dalam Meningkatkan Mutu Pendidikan - Putri, Sabrina Rida (Yayasan Sukma Bangsa, 2024)
This article analyzes the influence of leadership style on improving the quality of education in the educational environment. By focusing on the role of leaders in managing and directing educational institutions, this research aims to investigate the extent to which leadership style can influence the effectiveness and quality of education. The research method used includes literature analysis. The research results show that an effective leadership style can create a positive educational environment. Several leadership styles applied tend to influence on improving the quality of education. For example, a leadership style that is inspirational, inclusive, visionary, and supports the participation of school members can create a conducive environment for developing potential and improving the quality of education.